Effect of molting hormone, 20-hydroxyecdysone on blue swimming crab, Portunus pelagicus (Linnaeus, 1758) larval rearing - Mohamad Nor Azra Md Adib (Terengganu: Universiti Malaysia Terengganu, 2014)
Blue swimming crab, Portunus pelagicus commercial aquaculture production has not been established since the past few years and seeds production is problematic and unstable. The survival rate is low and mass mortality often occurs especially in larval stages. A study on the effects of molting hormone, 20-hydroxyecdysone (20E) during larval stages was carried out to establish the knowledge on the role of 20E hormone in improving the survival, growth and development of P. pelagicus culture. Newly hatched larvae of P. pelagicus were collected from larviculture and extracted for 20E level’s analysis by using high performance liquid chromatography (HPLC). The result shows that level of 20E varied between 2.65pg individual-1 to 9.02pg individual-1.